Optimization of vegetative growth conditions for submerged cultivation of edible medicinal mushroom Hericium erinaceus by Resonance surface methodology - Sakshi Khurana; Anil Sindhu; Sangeeta C. Sindhu; garg, Palak; Vikash Kumar; Ajay Singh (Mushroom Research, 2022)
Edible medicinal mushroom Hericium erinaceus commonly known as Lion’s mane contains various bioactive metabolites.  These metabolites are associated with many health benefits and used as nutraceuticals and pro-health goods. Therefore, the objective of this study was to optimize vegetative growth conditions at which metabolites production was maximum. In this study, conditions such as pH, temperature, and agitation of the fermenter were used to study the relative effect on biomass in the submerged medium. Initially, the biomass experiments were designed using the Box Behnken Design (BBD). A total of 17 trial runs with varying ranges were carried out. Vegetative growth condition variables were found to play a decisive role in determining the quantity of the total biomass production in submerged conditions. The response surface methodology (RSM) was further used to analyze the results and finally to optimize the relationship of growth conditions. The analysis showed that maximum biomass production (34.44g/l) was optimized at temperature 24.39 ℃, pH 6.38, and 147.42 rpm. The predicted maximal growth was within 0.130-1.49 percent error of the experimental data under these conditions. With R2>0.9, the model produces an acceptable outcome. Therefore, we concluded that these indicator parameters can be used for better production of mycelium biomass and metabolites, used as medicinal and pharmacological products.